2017
DOI: 10.15580/gjea.2017.3.112017170
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate Volatility and Fiscal Deficit in Nigeria: Any Causality? (1970-2016)

Abstract: This study investigated possible causal relationships between fiscal deficit and exchange rate in Nigeria. The study adopted the vector autoregression (VAR) econometric technique to analyze the time series data obtained from the Central Bank of Nigeria and other sources. The study amongst other findings, found long run relationship between exchange rate and fiscal deficit, irrespective of how the deficit is financed. The study also found joint causality running from fiscal deficit to exchange rate with feedbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The results revealed that there is a long-run relationship between budget deficit and the exchange rate in Sri Lanka. Nwaeze (2017) examined the relationship between fiscal deficits, modes of financing it and macroeconomic stability in Nigeria from 1970 to 2016. The study used inflation rate and exchange rate as proxies for macroeconomic stability whereas overall fiscal deficits, fiscal deficit financed by domestic borrowing, fiscal deficit financed by external borrowing, interest rate, money supply, foreign direct investment, and external reserve balance were used as the endogenous variables.…”
Section: Macmillin Andmentioning
confidence: 99%
“…The results revealed that there is a long-run relationship between budget deficit and the exchange rate in Sri Lanka. Nwaeze (2017) examined the relationship between fiscal deficits, modes of financing it and macroeconomic stability in Nigeria from 1970 to 2016. The study used inflation rate and exchange rate as proxies for macroeconomic stability whereas overall fiscal deficits, fiscal deficit financed by domestic borrowing, fiscal deficit financed by external borrowing, interest rate, money supply, foreign direct investment, and external reserve balance were used as the endogenous variables.…”
Section: Macmillin Andmentioning
confidence: 99%